Controls on Reactive Oxygen Species Cycles in Yellowstone Hot Springs: Implications for Biosignature Preservation on Mars - Hinman, Nancy W.; Mave, Megan A.; Powers, Leanne C.; Schmitt-Kopplin, Philippe; Cabrol, Nathalie A.; Gonsior, Michael (Frontiers in Astronomy and Space Sciences, 2022)
Early Earth and Mars had analogous environments. While life developed on our planet, the question of whether it did on Mars remains to be answered. Hot spring deposits are compelling targets for exploration because of their high habitability and potential to retain morphological and chemical biosignatures. As a result, with the current study herein, we aim to better understand biosignature preservation as it occurs in Fe-bearing hydrothermal systems. Understanding oxidation-reduction reactions involving Fe in hot springs is a key step in elucidating the preservation process. Fe reacts readily with reactive oxygen species (ROS), which are produced in hot spring surface waters through photochemical processes. Furthermore, Fe3+ can bind to cell membranes and preserve complex organic molecules (i.e. biomarkers). ROS formation is typically controlled by photoreactions with dissolved organic matter (DOM). However, Fe redox reactions more likely control ROS formation in these Fe-bearing systems. We deconvolved the relationship of ROS with Fe in hot springs and evaluated the role that DOM and dissolved organic sulfur (DOS) may have in ROS production. To better understand these coupled systems, field and laboratory experiments were conducted in hot springs of Yellowstone National Park. In situ H2O2 concentrations observed in these hot springs were comparable to, or higher than, those of other high-temperature systems. Reaction rates determined by measuring concentrations after specified time intervals varied based on water compositions and the presence of particulate or dissolved matter. Fe speciation (photochemical reactivity), concentration, and solubility further determined ROS cycling rates. Specifically, photochemically active Fe enhanced both ROS formation and decay rates depending on incident UV irradiance, and rates increased along with Fe concentration and solubility (i.e. in acidic conditions). Better understanding how ROS and Fe cycle in predominantly abiotic conditions will eventually aid in distinguishing between biosignatures and abiotic substances in the rock record.